2014
DOI: 10.3310/hsdr02410
|View full text |Cite
|
Sign up to set email alerts
|

The design of a survey questionnaire to measure perceptions and behaviour during an influenza pandemic: the Flu TElephone Survey Template (FluTEST)

Abstract: BackgroundDuring the 2009–10 influenza (flu) pandemic, surveys to assess behaviour among the general public were designed quickly and suffered from methodological deficits as a result. To facilitate survey work in a future pandemic we (1) identified variables relating to behaviour, perceptions and presence of symptoms that were of relevance to policy-makers and other public health experts; (2) tested and refined the wording of questions to measure these variables; (3) assessed the reliability of responses to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 25 publications
0
55
0
Order By: Relevance
“…Norms may be behavior cues to motivate adoption of protective behaviors and commonly widespread social distancing behaviors. 7,10 Despite a small sample size constrained by time and no funding, this survey provides useful insights on why frequent quarantine breaking occurred during this active outbreak. The findings also point to an urgent need for both improved public education on voluntary quarantine adherence and greater risk communication transparency by public health agencies, not only in South Korea, but also globally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Norms may be behavior cues to motivate adoption of protective behaviors and commonly widespread social distancing behaviors. 7,10 Despite a small sample size constrained by time and no funding, this survey provides useful insights on why frequent quarantine breaking occurred during this active outbreak. The findings also point to an urgent need for both improved public education on voluntary quarantine adherence and greater risk communication transparency by public health agencies, not only in South Korea, but also globally.…”
Section: Discussionmentioning
confidence: 99%
“…), and worry about MERS (eg, agreement on the statement, "I feel worried that I may be infected with MERS"), perceived self-efficacy in preventing MERS (eg, agreement on the statement, "I am confident that I could protect myself from contracting MERS"), trust in government action to control MERS (eg, agreement with the statement, "I trust the government to do what is needed to protect us from contracting MERS"), perceived social norms toward MERS prevention (what others are doing) (eg, agreement on the statement of "Most of my friends took measures to prevent against MERS"), attitudes toward quarantine (eg, agreement on the statement of "quarantine is not very effective to stop the spread of MERS"), and MERS-related anxiety (a 6-item scale). 6,7 All the above were responded to on 7-point (susceptibility, severity) or 4-point (MERS-related anxiety) or 5-point categorical response scales. Internal consistency (Cronbach's a) for the above core measures was generally acceptable ranging from 0.61 (for perceived social norms in MERS prevention) to 0.90 (for perceived susceptibility to MERS and worry about MERS) ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical trial data suggest that 47.9% of children who received the Fluenz tetra vaccine report a symptom (46). Survey data by our group suggested that we could assume equal sample sizes between those who do and do not expect symptoms (47). To detect this difference as significant at the 5% level with 85% power requires a total sample size of 180.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…The questionnaire was based on a similar questionnaire on COVID-19 ( 22) and other questionnaires on H1N1 ( 17,18), and Severe Acute Respiratory Syndrome, SARS ( 19) as well as concepts theories of health behaviors ( 25). The questionnaire takes about 5 minutes to complete.…”
Section: Questionnairementioning
confidence: 99%